Factors influencing the severity of pain in patients with peripheral diabetic neuropathy - Abdullah, Sinan Mohamed; Abdul Razak, Tariq; Nik Ahmad, Nik Nur Fatnoon; Mohamed, Abdul Hadi; Che Abdullah, Shahrin Tarmizi (Innovare Academic Sciences, 2017)
Objective: The principal aim of this study was to identify factors influencing the severity of peripheral diabetic neuropathy pain (PDNP), a symptom of the common neurological complication of diabetes mellitus, and peripheral diabetic neuropathy. Methods: A cross-sectional study was performed using two self-administered questionnaires among subjects recruited from outpatient clinics at Hospital Tengku Ampuan Afzan, Kuantan, Malaysia. The Neuropathic Pain-4 tool was used to evaluate the presence of PDNP, and the Short-Form McGill Pain Questionnaire (MPQ) was used to characterize and determine the severity of PDNP. Sociodemographic and clinical data were collected from the patients. Results: The MPQ indicated that most patients reported experiencing mild pain for all sensory pain descriptors other than throbbing and aching (mostly reported to be moderate) and hot-burning (mostly reported to be no pain). The severity of pain was found to be significantly related to the length of time for which the patients had suffered from diabetes in those patients who had been diagnosed over 10 years previously (p=0.04). Indian patients reported a higher severity of pain overall (p=0.04). No significant relationship was found between pain severity and any of the following factors: Type of diabetes (I or II), gender, smoking status, alcohol consumption, obesity, medication taken, or presence of other diseases. Conclusion: In this study, most patients with PDNP reported the severity of the pain to be “mild.” The pain severity may be influenced by a patient’s ethnicity and the length of time for which they have suffered from diabetes.